MODIFIKASI SOLAR DAN BIOSOLAR MENJADI BAHAN BAKAR BERKUALITAS PERTAMINA DEX - , IKA KUSUMA NUGRAHENI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Modification of Solar and Biosolar into fuel with Pertamina DEX Quality had been carried out. In this research, Solar and Biosolar are product of Pertamina. The physical properties test showed that Pertamina DEX has better quality than Solar and Biosolar. The result of component analysis showed that both of fuels have similar chromatogram, but Pertamina DEX has narrow pattern than Solar and Biosolar. The light and heavy fractions in Solar and Biosolar were separated by distillation. The results of this modification were analyzed in their density, viscosity and heat of combustion. Based on the four fraction of Biosolar, the analysis result showed that 2nd (Bp. 45-68 oC), 3rd (Bp. 46-70 oC), and 4th (Bp. 146-150 oC) fractions have the same retention time with Pertamina DEX. Based on three fractions of Solar , the analysis result showed that 2nd (Bp. 64-65 oC) and 3rd (Bp. 66-50 oC) fractions have the same retention time with Pertamina DEX. The analysis of density and viscosity results showed that modification produced fuel with lower density and viscosity, but higher on heat of combustion. The results showed that Solar and Biosolar modification characters still have distinct characters with Pertamina DEX.